Replenishing the Odyssey - Aćamović, Bojana (ELOPE (Ljubljana), 2020)
The paper focuses on Margaret Atwood's novel The Penelopiad and John Barth's short stories "Menelaiad" and "Anonymiad", comparing the approaches of the two authors in their postmodernist retellings of Homer's Odyssey. Both Atwood and Barth base their narratives on minor episodes from this epic, with its less prominent or unnamed characters assuming the roles of the narrators. Using different postmodernist techniques, the authors experiment with the form and content of the narration, combine different genres, and demythologize the situations and characters. In their re-evaluations and reinterpretations of the Odyssey, they create works which epitomize Barth's notion of postmodernist fiction as a literature of replenishment. The comparative analysis presented in this paper aims to highlight the ways in which Atwood and Barth challenge the old and add new perspectives on Homer's epic, at the same time confirming its relevance in the postmodern context.
Keywords: Atwood, Margaret; Barth, John; mitologija; mythology; Odiseja; Odyssey; postmoderna; postmodernism